Tasawuf ‘amali - Ilfina, Firda Suci Chanifatul; Soleh, Achmad Khudori (Maliki Interdisciplinary Journal, 2024)
In the current era of globalization, Sufism is an appropriate source of inspiration and spirituality to guarantee ultimate truth. By practicing the teachings contained in the basic teachings of Sufism 'amali, namely faith, Islam, and ihsan, each of which cannot be separated. Islam is worthless without faith, and faith is incomplete without ihsan. Each of the three components has two other meanings, namely in Islam there is faith and ihsan, in faith there is ihsan, and in ihsan there is Islam and Iman. The purpose of writing this article is to discuss in more detail the Sufism 'amali taught by Sheikh Abdul Qadir al-Jailani. The result of this writing is that there are seven basic rules of the Qadiriyah congregation, namely mujahadah, resignation, noble character, gratitude, patience, and honesty.